2022
DOI: 10.1055/a-1969-2440
|View full text |Cite
|
Sign up to set email alerts
|

Use of Milk Thistle in Farm and Companion Animals: A Review

Abstract: Milk thistle, Silybum marianum, is a medicinal plant grown for its bioactive compounds with well-documented antioxidant and hepatoprotective properties. Milk thistle has a well-established pharmacological reputation for treatments of human liver disease, but it is also used in animals. This review summarizes the experimental evidence of milk thistle’s effects on animals when administered as silymarin extract (feed additive) or a feed ingredient, if administered as seed or expeller/cake with the seed residue st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…The pharmacological potential of MT is well documented by existing data that confirm the safety and tolerability of its herbal preparations in various settings related to hepatic disorders, and in farm animals to support their performance and health [29]. Detailed information on the multifunctional and multitarget activity and the potential mechanism of action of MT and derivative products were reported in the European Medicines Agency (EMA) report [25] and by Tedesco and Guerrini [29]. In the liver, SIL suppresses the increase in the hepatic enzymes, such as ALT, AST, and ALP, during liver damage, associated with the ribosomal RNA synthesis induced by SIL, improving liver regeneration and preventing the transformation of stellate hepatocytes into myofibroblasts [30][31][32], conducing to the restoration of normal liver functions and enzymes production at a normal value [33,34].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The pharmacological potential of MT is well documented by existing data that confirm the safety and tolerability of its herbal preparations in various settings related to hepatic disorders, and in farm animals to support their performance and health [29]. Detailed information on the multifunctional and multitarget activity and the potential mechanism of action of MT and derivative products were reported in the European Medicines Agency (EMA) report [25] and by Tedesco and Guerrini [29]. In the liver, SIL suppresses the increase in the hepatic enzymes, such as ALT, AST, and ALP, during liver damage, associated with the ribosomal RNA synthesis induced by SIL, improving liver regeneration and preventing the transformation of stellate hepatocytes into myofibroblasts [30][31][32], conducing to the restoration of normal liver functions and enzymes production at a normal value [33,34].…”
Section: Introductionmentioning
confidence: 94%
“…Mycotoxicosis inhibits poultry health, and consequently their performance, such as growth reducing feed consumption, digestion, absorption, enzymatic activity, and protein metabolism. In some studies, the MT potential to improve or prevent further worsening of the performance and quality parameters of products, such as poultry meat [29,75], was investigated when the performance can be worsened by MyT intoxication.…”
Section: Influence Of Sil On Immunological Parameters In Myt-poisoned...mentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the literature sources revealed that over recent decades, drugs made from S. marianum have been successfully used to treat patients with liver pathologies, both animals and humans. Experimental in vitro and in vivo studies exhibited strong hepatoprotectory effect of S. marianum as a fodder or a supplement to fodder for agricultural animals and poultry (Khaleghipour et al, 2019;Gutyj et al, 2022;Tedesco & Guerrini, 2022;Lieshchova & Brygadyrenko, 2023). Hepatoprotectors are important means for treating animals and humans with liver pathologies.…”
Section: Introductionmentioning
confidence: 99%